Population genetic structure and interspecific differentiation between Acer davidii Franchi. and A. morrisonense Hayata (Aceraceae) based on SSR markers. (April 2017) - He, Yan-Ling; He, Ying; Gong, Lin-Lin; Fang, Min-Feng; Li, Zhong-Hu
Abstract: Acer davidii Franch. and A. morrisonense Hayata are two important forest tree species (Aceraceae) endemic to mainland China and the Taiwan area, respectively. To investigate population structure and interspecific differentiation between them, we characterized a set of novel microsatellite markers using Illumina sequencing technology. The cross-species amplification analysis showed that 11 out of 21 polymorphic SSR primers of A. davidii also exhibited polymorphisms in A. morrisonense . At the species level, A. davidii has a slightly higher genetic diversity (mean observed heterozygosity, H O  = 0.180) than A. morrisonense ( H O  = 0.119). AMOVA showed that most of the variations in A. davidii occurred among individuals within populations and within individuals. Bayesian clustering analyses demonstrated that the two maple species formed two clear genetic lineages. PCoA showed that A. davidii and A. morrisonense were significantly divided into two genetic groups. In addition, asymmetrical weaker gene flow was detected among the two forest tree species. These results suggest that the long term geographic isolation between the mainland and Taiwan may have resulted in a high level of genetic differentiation between these two important maple species. Highlights: The population structure and differentiation between Acer davidii and A. morrisonense were determined based on SSR markers. A high level of interspecific differentiation was identified between the two maple species. Long term geographic isolation may have driven species differentiation between the two forest species.